META-NET Strategic Research Agenda for Multilingual Europe 2020 - Rehm, Georg; Uszkoreit, Hans (White Paper Series, 2013)
In everyday communication, Europe's citizens, business partners and politicians are inevitably confronted with language barriers. Language technology has the potential to overcome these barriers and to provide innovative interfaces to technologies and knowledge. This document presents a Strategic Research Agenda for Multilingual Europe 2020. The agenda was prepared by META-NET, a European Network of Excellence. META-NET consists of 60 research centres in 34 countries, who cooperate with stakeholders from economy, government agencies, research organisations, non-governmental organisations, language communities and European universities. META-NET's vision is high-quality language technology for all European languages. "The research carried out in the area of language technology is of utmost importance for the consolidation of Portuguese as a language of global communication in the information society." - Dr. Pedro Passos Coelho (Prime-Minister of Portugal) "It is imperative that language technologies for Slovene are developed systematically if we want Slovene to flourish also in the future digital world." - Dr. Danilo Türk (President of the Republic of Slovenia) "For such small languages like Latvian keeping up with the ever increasing pace of time and technological development is crucial. The only way to ensure future existence of our language is to provide its users with equal opportunities as the users of larger languages enjoy. Therefore being on the forefront of modern technologies is our opportunity." - Valdis Dombrovskis (Prime Minister of Latvia) "Europe's inherent multilingualism and our scientific expertise are the perfect prerequisites for significantly advancing the challenge that language technology poses. META-NET opens up new opportunities for the development of ubiquitous multilingual technologies." - Prof. Dr. Annette Schavan (German Minister of Education and Research)